Resonant inelastic x-ray scattering reveals hidden local transitions of the aqueous OH radical - Kjellsson, L. (2020)
Resonant inelastic x-ray scattering (RIXS) provides remarkable opportunities to interrogate ultrafast dynamics in liquids. Here we use RIXS to study the fundamentally and practically important hydroxyl radical in liquid water, OH(aq). Impulsive ionization of pure liquid water produced a short-lived population of OH(aq), which was probed using femtosecond x-rays from an x-ray free-electron laser. We find that RIXS reveals localized electronic transitions that are masked in the ultraviolet absorption spectrum by strong charge-transfer transitions-thus providing a means to investigate the evolving electronic structure and reactivity of the hydroxyl radical in aqueous and heterogeneous environments. First-principles calculations provide interpretation of the main spectral features.